Inadequate menstrual health management and human rights - Hartley, Gemma-Maé (Rhodes University, Faculty of Humanities, Department of Political and International Studies)
Various human rights bodies have suggested that Inadequate Menstrual Health Management (MHM) could contribute to violations of human rights or, at the very least, is connected to the fulfilment of human rights. Despite recognition of this, there has not been thorough analysis of whether inadequate MHM is a violation of human rights, particularly in political discussions on the philosophy of human rights. Using a liberal cosmopolitan framework, this thesis attempts to bridge this gap and, ultimately, to argue that inadequate MHM constitutes a violation of human rights. This assertion brings with it various complications due to the heavily contested nature of human rights, their correlative duties, and the requirements for a lack of fulfilment to be considered a violation. I address each complication in turn. I argue that the traditional approach to human rights violations fails to consider the various ways that human rights are violated in our contemporary, globalised world. I suggest that structural violations of human rights should not be ruled out, particularly when we consider severe poverty and its by-products. Ultimately, the question of inadequate MHM is concerned with the content of human rights. If inadequate MHM were a violation, it would be a violation of women's socio-economic rights. However, both group rights and socio-economic rights are contested. This thesis therefore justifies these rights. Group-differentiated rights are argued to be necessary for substantive equality. This is particularly the case when we consider the various risks women face simply because they are women. Women therefore need special protections and provisions for their human rights to be fulfilled. Socio-economic rights are necessary for the well-being and dignity of individuals everywhere. We can justify them even if they are costly, vague, and demanding on states, as critics argue they are. Therefore, if we can accept socio-economic rights and women's rights, we can argue that inadequate MHM is a structural violation of human rights. Thinking about inadequate MHM in this way means we can respond to it with a level of urgency. This has the potential to improve the well-being, development, and dignity of women.
Keywords: Menstrual hygiene management; Human rights; Political philosophy; Transgression; Women -- Social conditions; Economic, social and cultural rights